2018
DOI: 10.1186/s12878-018-0125-0
|View full text |Cite
|
Sign up to set email alerts
|

A ten year review of the sickle cell program in Muhimbili National Hospital, Tanzania

Abstract: BackgroundAfrica has the highest burden of Sickle cell disease (SCD) but there are few large, systematic studies providing reliable descriptions of the disease spectrum. Tanzania, with 11,000 SCD births annually, established the Muhimbili Sickle Cell program aiming to improve understanding of SCD in Africa. We report the profile of SCD seen in the first 10 years at Muhimbili National Hospital (MNH).MethodsIndividuals seen at MNH known or suspected to have SCD were enrolled at clinic and laboratory testing for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 40 publications
(36 reference statements)
1
64
0
Order By: Relevance
“…Full blood counts were obtained at the time of recruitment. For those who had been enrolled in a previous study, 21 we obtained from that database available daytime oxygen saturation (SpO 2 ) measured in clinic by pulse oximetry, hemoglobin level, reticulocyte count, and indirect bilirubin. Where daytime oxygen saturation and hemoglobin were available on the same day, arterial oxygen content (CaO 2 ) was calculated as:…”
Section: Demographic and Clinical Variablesmentioning
confidence: 99%
“…Full blood counts were obtained at the time of recruitment. For those who had been enrolled in a previous study, 21 we obtained from that database available daytime oxygen saturation (SpO 2 ) measured in clinic by pulse oximetry, hemoglobin level, reticulocyte count, and indirect bilirubin. Where daytime oxygen saturation and hemoglobin were available on the same day, arterial oxygen content (CaO 2 ) was calculated as:…”
Section: Demographic and Clinical Variablesmentioning
confidence: 99%
“…We recruited research participants enrolled in an urban hospital-based study aiming to understand genetic determinants of clinical heterogeneity of sickle cell disease (SCD) in Tanzania [18,19]. At the time of recruitment, the study consisted of 3751 individuals with SCD, 1779 were between 5 and 17 years of age with almost a 50/50 gender distribution [20]. Participants for the study reported here, were recruited through adult and paediatric clinics at Muhimbili National Hospital.…”
Section: Sampling and Recruitmentmentioning
confidence: 99%
“…Furthermore, when we performed the analysis excluding three patients who had adenotonsillectomy for OSA after starting HU (in these children improvements of SpO 2 could depend on relief of upper airway obstruction rather than HU), differences in nocturnal SpO 2 remained significant. Regarding other potential confounders, over the study period, the centres involved did not apply major changes in the standards of care for SCD patients (apart from increasing use of HU), and the SpO 2 would have been expected to decrease, rather than increase, by time 5 21 34. Therefore, it is unlikely that variables not taken into account had a relevant influence on changes in oxygen saturation in patients on HU.…”
Section: Discussionmentioning
confidence: 99%